2019
DOI: 10.1097/mpa.0000000000001404
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Radiomics and Risk of Lymph Node Metastasis in Pancreatic Ductal Adenocarcinoma

Abstract: Supplemental digital content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 33 publications
0
35
0
Order By: Relevance
“…reported that the greater attenuation differential between lesions and normal pancreas during the arterial phase compared to venous. Bian et al (23). also reported a significant positive association between the arterial-phase-based radiomics Radscore and the risk of LN metastasis in pancreatic ductal adenocarcinoma.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…reported that the greater attenuation differential between lesions and normal pancreas during the arterial phase compared to venous. Bian et al (23). also reported a significant positive association between the arterial-phase-based radiomics Radscore and the risk of LN metastasis in pancreatic ductal adenocarcinoma.…”
Section: Discussionmentioning
confidence: 93%
“…Considering the radiomics feature could be extracted from the single cross section (two dimensional, 2D) or multi-slices (three dimensional, 3D) of the tumor in CT images, the reported radiomics-based pancreatic cancer studies have either applied 2D segmentation (20) or 3D whole-tumor segmentation (14,(21)(22)(23)(24)(25). However, whether to select 2D regions of interest (ROIs) or 3D ROIs still remains unclear for invasive behavior prediction in pSPN.…”
Section: Introductionmentioning
confidence: 99%
“…Although to the best of our knowledge, there are no published studies indicating that pancreatic atrophy is an independent factor for LN status in PDAC, we have reason to believe that it does have a potential association with LNM in such patients. Compared with the previous studies using radiomics to evaluate the LN status for PDAC patients ( 49 , 50 ), we believe that our approach offers advantages for the following reasons: (1) We performed a stratified analysis to further evaluate the prediction efficiency of our model, which can determine the clinical application potential of our model under different conditions. (2) In addition to the CT-reported LN status, we adopted more conventional CT imaging signs in the clinical model.…”
Section: Discussionmentioning
confidence: 99%
“…Feature selection comprised three steps: variance analysis, spearman correlation analysis, and least absolute shrinkage and selection operator method (LASSO) logistic regression algorithm. This method has been shown to be effective in prior radiomics studies [22]. A retrospective power analysis was performed.…”
Section: Radiomics Workflowmentioning
confidence: 99%